What Factors Predict Improvements in Outcomes Scores and Reoperations After the Bernese Periacetabular Osteotomy? - Beaulé, Paul E. (Clin Orthop Relat Res, 2014)
BACKGROUND: The Bernese periacetabular osteotomy (PAO) has entered its fourth decade and is frequently used for corrective osteotomy in patients with acetabular dysplasia. Although our capacity to preserve the joint after corrective osteotomy is excellent, gaining a better understanding on how well patients function after this surgery is important as well. QUESTIONS/PURPOSES: (1) What changes in patient-reported outcomes scores occur in patients treated with PAO for hip dysplasia in the setting of a single-surgeon practice? (2) What are the predictors of clinical function and survivorship? METHODS: All 67 patients presenting to a single surgeon’s clinic with hip dysplasia treated with PAO between October 2005 and January 2013 were prospectively followed. Baseline demographic data as well as pre- and postoperative radiographic and functional measurements were obtained with a minimum of 1-year followup. Radiographic criteria included Tönnis grade, Tönnis angle, minimum joint space width, center-edge angle, presence of crossover sign, medial translation of the hip center, and alpha angle. We also used validated outcome measures including the WOMAC, the UCLA Activity Scale, and the SF-12. Multiple regression analysis was used to determine predictors of functional outcome scores. RESULTS: There were increases in WOMAC, UCLA, and SF-12 Physical scores. Higher preoperative alpha angle was associated with a lower postoperative WOMAC score (β = −0.47; 95% confidence interval [CI], −0.92 to −0.02; R(2) = 0.08; p = 0.04). The 5-year Kaplan-Meier survivorship was 94.1% (95% CI, 90.7–97.5) with reoperation (ie, hip arthroscopy and/or total hip arthroplasty) used as the endpoint for failure. With the limited numbers available, we could not identify any demographic or radiographic factors associated with reoperation. CONCLUSIONS: Overall survivorship for the PAO at our center at 5 years is comparable to other clinical series with overall functional scores improving. A greater alpha angle preoperatively was associated with poorer patient-reported outcome scores. Further research is needed to determine how and when intraarticular cartilage damage associated with dysplasia needs to be addressed. LEVEL OF EVIDENCE: Level IV, therapeutic study.